Draft Genome Assembly Dataset Of The Basidiomycete Pathogenic Fungus, Ganoderma Boninense - Suhaila Sulaiman; Nur Qistina Othman; Joon Sheong Tan; Yang Ping Lee (Elsevier, 2024)
Data in Brief Volume 29, April 2020, 105167